Meningkatkan Motivasi Belajar Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament - Kasim, Rahmat Rajib; Badu, Syamsu Qamar; Yahya, Lailany (Scimadly Publishing, 2024)
This research is motivated by the low motivation to learn mathematics in mathematics in class VII-3 of SMP Negeri 1 Telaga Jaya. This study aims to increase students' motivation to learn mathematics through the use of cooperative learning models of the Teams Games Tournament (TGT) type. This type of research is classroom action research (PTK). Kemmis and Mc Design. Taggart was used for this research. This study used data collection techniques, namely observation and questionnaires. Teacher observation sheets, student observation sheets, and learning motivation questionnaires were used to view the data. Plan, report, observe, and think about what you have learned are all part of the research process. The research was conducted in two parts. The results showed that teacher activity in learning increased by 88.88%, and student activity increased by 93.75%. Student motivation also increased, with 10 students getting a score of 34.38% in the